PENGARUH SERVICE QUALITY, CUSTOMER VALUE, CITRA PERUSAHAAN DAN SWITCHING COST TERHADAP LOYALITAS KONSUMEN DENGAN EXPERIENTIAL MARKETING SEBAGAI VARIABEL INTERVENING PADA PT ASURANSI JASINDO KANTOR CABANG JEMBER - Samekto, Angkat; Suroso, Imam; Wulandari, Dessy (Relasi : Jurnal Ekonomi, 2016)
The aim of this study was to examine the effect on service quality, customer value, corporate image on experiential marketing PT Asuransi Jasa Indonesia; to examine the influence of service quality, customer value, corporate image, switching cost on customer loyalty PT Asuransi Jasa Indonesia and to examine the effect of experiential marketing on customer loyalty PT Asuransi Jasa Indonesia. The object under study is a customer of PT Asuransi Jasa Indonesia. This study was to describe the facts and to test the hypothesis to see relationships between variables, The design of this research study explanation (explanatory research / confirmatory research). Sampling technique used in this study was purposive sampling. The population in this study is limited to the retail consumer segment is the insurance services PT.Asuransi Jasindo Jember fire insurance policy holders, vehicle insurance and miscellaneous insurance in 2013 , amounting to 986 people.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />